Characterization of a novel R7-specific gene in the drosophila visual system - Kaçmaz, Güner. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
The proper functioning of the nervous system depends on the correct specification of many different cell types and the establishment of proper connections between neurons during development. The visual system of Drosophila represents a good model to study these mechanisms. The Drosophila eye consists of 800 small eye-like structures called ommatidia each containing eight photoreceptors (PRs). Photoreceptors are grouped into two; outer and inner, and each expresses sensory receptor molecule called Rhodopsin (Rh). In an attempt to identify novel genes playing a role in photoreceptor specification, the enhancer trap line for CG7985 showing an R7-specific expression was selected. The aim of this thesis was to characterize this gene functionally to understand its role in visual system development. CG7985 was shown to encode a hexosaminidase enzyme that is conserved in evolution. Hexosaminidases are involved in the hydrolysis of GM2 gangliosides. The human homolog of CG7985, HexDC, has not been investigated extensively, while other well-studied homologs are represented by HexA and HexB, which give rise to diseases like Tay - Sachs and Sandhoff that are characterized by symptoms that include blindness, loss of motor function, paralysis and psychosis. As CG7985 has not been studied previously, we generated tools necessary for its functional analysis. Using Flp/FRT recombination a mutant has been generated. In addition, a transgenic line carrying a targeting construct for homologous recombination was generated. A UAS-line for ever-expression analyses was generated. To identify the endogenous expression of CG7985 a genomic BAC construct encoding a fusion protein CG7985::GFP has been engineered and transgenic flies carrying this construct have been analyzed. Initial analyses of the mutant did not reveal any phenotypes affecting Rh choice in the R7 cell. Western blot analysis of R7-specific and glycosylated proteins did not reveal any changes in the glycosylation pattern of these proteins. More studies are needed to elucidate the function of CG7985 protein.
Keywords: Drosophila melanogaster.; Cell adhesion.